2015
DOI: 10.1080/21645515.2015.1069931
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immune responses to H5N1 inactivated influenza vaccine among individuals previously primed with H5N2 live attenuated influenza vaccine

Abstract: During the past decade, a number of H5 subtype influenza vaccines have been developed and tested in clinical trials, but most of them induced poor serum antibody responses prompting the evaluation of novel vaccination approaches. One of the most promising ones is a “prime-boost” strategy, which could result in the induction of prompt and robust immune responses to a booster influenza vaccine following priming with homologous or heterologous vaccine strains. In our study we evaluated immunogenicity of an adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
15
0
3
Order By: Relevance
“…In contrast, in naïve individuals, two doses were required for a significant immune response to develop (TABLE 6). The antibodies induced by this prime-boost strategy were of high quality, as measured by their avidity and affinity [52][53][54]. Thus, such a vaccination regimen could have significant advantages in terms of availability and ease of administration of the priming vaccine and possibility of dose sparing for the booster vaccine.…”
Section: Immunogenicity Of Pandemic Laivsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in naïve individuals, two doses were required for a significant immune response to develop (TABLE 6). The antibodies induced by this prime-boost strategy were of high quality, as measured by their avidity and affinity [52][53][54]. Thus, such a vaccination regimen could have significant advantages in terms of availability and ease of administration of the priming vaccine and possibility of dose sparing for the booster vaccine.…”
Section: Immunogenicity Of Pandemic Laivsmentioning
confidence: 99%
“…These data prompted evaluation of the ability of pandemic LAIVs to prime for immunological memory, which can be unmasked by administration of a suboptimal dose of pandemic IIV several months or years later. To date, three studies have evaluated the priming effect of pandemic LAIVs: two with A/AA-backbone (H5N1 and H7N7) and one with Len/17 backbone (H5N2) [46,52,53]. All three studies revealed that priming with pandemic LAIV induced a long-lasting B-cell immunological memory in humans against antigenically related influenza virus, which was characterized by more prompt and vigorous antibody production to a single suboptimal dose of inactivated vaccine given 19-50 months later (TABLE 6).…”
Section: Immunogenicity Of Pandemic Laivsmentioning
confidence: 99%
“…Поэтому у участвовавших в нашем исследовании праймированных волонтеров ин-тенсивность накопления сывороточных антител к праймирующему вирусу А (H5N2) оказалась выше, чем к вакцинному вирусу А (H5N1), с ко-торым они встретились впервые. Необходимо от-метить значительный бустирующий эффект ИГВ H5N1 у праймированных ЖГВ H5N2 волонтеров, в отношении продукции сывороточных антител к вирусу H5N1, поскольку, как показано нами ра-нее, у непраймированных волонтеров синтез этих антител, в ответ на двойную инокуляцию ИГВ H5N1, оказался весьма низким [13]. Однако ко-личественные показатели (СГТ) секретируемых антител к обоим вирусам практически не отли-чались, поскольку, скорее всего, они проявляли специфичность только к общему гемагглютини-ну Н5, без «наслоения» кросс-реактивных анти-тел к консервативным белковым структурам вируса, выявляемым при исследовании в ИФА сывороточных антител.…”
Section: поствакцинальная секреция антител в-лимфоцитами In Vitro In unclassified
“…The idea to administer of a combination of two different types of influenza vaccines led to the development of novel vaccination approach – so called prime–boost strategy, which could result in induction of significant immune response to a booster IIV following priming with homologous or heterologous LAIV [53-55]. Similar to these prime–boost studies, assessment of immune responses to tT (H5N1) inactivated influenza vaccine among individuals previously primed with Len–tT (H5N2) LAIV was performed [56]. Data revealed that priming with Len–tT LAIV induced a long–lasting B–cell immunological memory in subjects against antigenically related influenza virus, which was characterized by more prompt and vigorous antibody production to a single dose of H5–IIV given 18 months later.…”
Section: Introductionmentioning
confidence: 99%